Physical Work Environment And Employee Performance - eva mirza; Ridho Muarief; Nur Rohmad Arip Wicaksono (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2022)
The work environment is very important in the business world because the work environment can affect employee motivation in carrying out tasks which in turn has an impact on the resulting performance. Writing this Final Project aims to find out how the physical work environment in the Consumer Service Unit at PT Telkom Indonesia (Persero) Tbk Madiun Telecommunication Region is based on the theory of the physical work environment by Asriel, et al. (2016). The research method used is descriptive qualitative, with data obtained through interviews, observation, and documentation. Data processing techniques are carried out by presenting the data, then a discussion is carried out by comparing the factors of the physical work environment which include color, lighting, sound control, air, and music. From the discussion, it was found that in choosing color accents on doors, windows, and wall banners using bright colors, the color of the furniture contrasts with the color of the walls. Lighting can reach the entire room, but some lights need improvement and some employees are dazzled in the monitor screen area. In terms of sound conditions, there is noise and sound disturbance that comes from the sound of vehicles from outside and the sound of people talking in the room. Overall air regulation is good, there are functioning AC facilities and no air pollution occurs. Music is not always played but it depends on the wishes of the employees, as well as various types of music.